(untitled) (Journal of Mechanical Engineering, 2013)
In this study, Biodiesel -Dimethyl Ether (BDE) and Biodiesel Ethanol (BE) were tested in a 4-cylinderdirect-injection diesel engine to investigate the performance and emission characteristics of the engine underfive engine loads at the maximum torque. The engine speed was maintained at 1500 rpm. Here the jatropha oilis used as a non edible oil to produce the biodiesel. The ethanol and dimethyl ether is used as an additive toenhance the engine combustion. The BDE 5 (biodiesel 95% and dimethyl ether 5%) , BDE 10 (biodiesel 90%and dimethyl ether 10%) BDE 15(biodiesel 85% and dimethyl ether 15%) BE5 (biodiesel 95% and ethanol 5%),BE10 (biodiesel 90% and ethanol 10%) and BE15 (biodiesel 85% and ethanol 15%) were tested in the engine.The results indicate that when compared with neat jatropha, the engine performance increased and emissionlevel decreased with adding the ethanol and diethyl ether with methyl ester of jatropha oil. In comparison withneat jatropha, the BDE5 and BE15 blends have higher brake thermal efficiency (BTE) of 12% and 13%respectively. The experimental results showed that the CO, HC emission is decreased and NOx emission isincreased for higher blends of additives. The brakes specific fuel consumption (BSFC) decreased for BDE5 andBE5 compared to other combination of fuel. DOI: http://dx.doi.org/10.3329/jme.v42i1.15941